Forests, People and Conflict: A Socio-Ecological Analysis of the 'All Eyes on Papua' Case - Jasmine, Humaira; Harahap, Rahma Hayati; Saputra, Dony; Destrianti, Febrina (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2025)
The case of “All Eyes on Papua” is one concrete example where forests, people and conflict meet in a series of events that affect each other. “All Eyes on Papua” symbolizes global resistance and attention to the situation in Papua, especially related to forest exploitation and neglect of the rights of indigenous peoples living there. From a socio-ecological perspective, such conflicts not only damage the relationship between humans and nature, but also cause significant ecological damage. This journal aims to analyze the case of “All Eyes on Papua,” to better understand how conflicts that occur in natural resource-rich regions such as Papua cannot be separated from the wider global context. This research is qualitative in nature with a literature review approach. Primary sources include official documents, government reports, and statistical data related to deforestation and environmental policies in Papua. Secondary sources include scientific literature, articles, books, and reports from non-governmental organizations (NGOs) related to environmental issues, indigenous peoples' rights, and natural resource conflicts. The results of this study show that the conflicts that occur in Papua are closely related to global dynamics involving economic, political and ecological interests. The socio-ecological approach reveals that the exploitation of natural resources in Papua, fueled by multinational corporations and other global actors, has threatened the sustainability of the ecosystem as well as the rights of indigenous peoples.